INTRODUCTION TO QUALITY SYSTEM - Sulaiman Haji Hasan; Sivaprakasam Thamizhmanii; Ibrahim Masood (2019)
The book contains conceptual design of Quality Management System (QMS). This book is first attempt towards introducing QMS and related fields. In order to learn all the quality concepts one has to refer to many books. It has been long term ambition to provide a simple basic book on QMS and it is our maiden attempt. This book is hoped to trigger interest of those who want to move forward in their career through QMS. One simple philosophy adopted is that you will learn by doing. It gives simple, clear presentation of concepts, tools and applications in the field of QMS. It is hoped that this book in its current format and form will fulfill the needs of the students. The authors are welcomed and will be grateful all valuable comments, suggestions and errors to enable improvement in the latter edition of this book.